To Find a Seat: Tracing the Ideoscape of Seats in the Pathars’ Lifeworld in Penang - Raman, Sanjeh Kumar; Zakaria, Safial Aqbar (UI Scholars Hub, 2023)
This article examines the roles taken by seats in the buildings that form the lifeworld of Pathars—traditional Tamil goldsmiths—as an ideoscape following their migration to Penang during the British colonial period in the 19th century. This study used a phenomenological ethnography method to bring Pathars’ lived experiences with their physical environment to the forefront, highlighting the subjectiveness of architecture that shapes their lifeworld. The ideoscape of seats is analysed in themes to examine the power and politics of seats in the Pathars’ lifeworlds, including present-day migrant workers. To find a seat is a metaphor that elicits discussion on Pathars’ existential lives and highlights how this community has attempted to negotiate its way as agents of change or to bring the agency to their position in creating spatial norms in place amidst the state reifying its enclaves with essentialised notions of ethnic identity, following the formation of nation-states.